PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI SMAN 1 BANGUN PURBA - -, Pebriani; -, Arcat; Afri, Lusi Eka (Universitas Pasir Pengaraian, 2015)
This research aimed to determine the effect of cooperative learning model Student Teams Achievement Division(STAD) to grade students mathematics learning outcomes kelas XI SMAN 1 Bangun Purba. In this study theformulation of the problem is